Serial measurements of N-terminal pro-brain natriuretic peptide in patients with coronary heart disease. - Dhayana Dallmeier; Michael J Pencina; Iris Rajman; Wolfgang Koenig; Dietrich Rothenbacher; Hermann Brenner (PLoS ONE)
Objective To assess the prognostic value of 12-months N-Terminal Pro-Brain Natriuretic Peptide (NT-proBNP) levels on adverse cardiovascular events in patients with stable coronary heart disease. Methods NT-proBNP concentrations were measured at baseline and at 12-months follow-up in participants of cardiac rehabilitation (median follow-up 8.96 years). Cox-proportional hazards models evaluated the prognostic value of log-transformed NT-proBNP levels, and of 12-months NT-proBNP relative changes on adverse cardiovascular events adjusting for established risk factors measured at baseline. Results Among 798 participants (84.7% men, mean age 59 years) there were 114 adverse cardiovascular events. 12-months NT-proBNP levels were higher than baseline levels in 60 patients (7.5%) and numerically more strongly associated with the outcome in multivariable analysis (HR 1.65 [95% CI 1.33-2.05] vs. HR 1.41 [95% CI 1.12-1.78], with a net reclassification improvement (NRI) of 0.098 [95% CI 0.002-0.194] compared to NRI of 0.047 [95% CI -0.0004-0.133] for baseline NT-proBNP levels. A 12-month 10% increment of NT-proBNP was associated with a HR of 1.35 [95% CI 1.12-1.63] for the onset of an adverse cardiovascular event. Subjects with a 12-month increment of NT-proBNP had a HR of 2.56 [95% CI 1.10-5.95] compared to those with the highest 12-months reduction. Conclusions Twelve-months NT-proBNP levels after an acute cardiovascular event are strongly associated with a subsequent event and may provide numerically better reclassification of patients at risk for an adverse cardiovascular event compared to NT-proBNP baseline levels after adjustment for established risk factors.